RF and microwave balun-filter on dual-mode ring or patch resonator - Wan, Chenxin (2013)
The researches of filter designs have been widely conducted as the filter is a necessary component for signal processing to get rid of noise and obtain the signal with desired frequency band. The filter would be implemented with lumped elements as well as transmission lines. The structure of the circuit and parameter values of these elements determine the type of filter, its bandwidth, order and return level.